2009
DOI: 10.1111/j.1471-4159.2009.06272.x
|View full text |Cite
|
Sign up to set email alerts
|

Hypothalamic neuronal histamine signaling in the estrogen deficiency‐induced obesity

Abstract: Menopause is one of the triggers that induce a variety of agerelated diseases such as osteoporosis, atherosclerosis, and obesity (Genazzani and Gambacciani 2001). The incidence of obesity is higher in post-menopausal women than in agematched pre-menopausal women; this increase is thought to be associated with the decline of estrogen levels after menopause. In fact, estrogen replacement therapy is an effective treatment to reduce body weight and fat accumulation in post-menopausal women (Svendsen et al. 1995). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 47 publications
(90 reference statements)
0
11
0
Order By: Relevance
“…These intriguing findings were not altogether unexpected, as earlier rodent studies had shown that supplemental histidine tends to inhibit food intake, via an impact on the hypothalamus that is mediated by the neurotransmitter histamine 3–6. Acting via H1 receptors in the ventromedial and paraventricular hypothalamic nuclei, histamine suppresses feeding behaviour, promotes adipocyte lipolysis via sympathetic activation and raises metabolic rate 3 7 8.…”
Section: Brain Histamine Influences Appetite and Metabolic Ratementioning
confidence: 79%
“…These intriguing findings were not altogether unexpected, as earlier rodent studies had shown that supplemental histidine tends to inhibit food intake, via an impact on the hypothalamus that is mediated by the neurotransmitter histamine 3–6. Acting via H1 receptors in the ventromedial and paraventricular hypothalamic nuclei, histamine suppresses feeding behaviour, promotes adipocyte lipolysis via sympathetic activation and raises metabolic rate 3 7 8.…”
Section: Brain Histamine Influences Appetite and Metabolic Ratementioning
confidence: 79%
“…No such effect was observed after microinjections into the VMH or the medial preoptic area. Furthermore, estradiolinduced suppression of feeding is partially attenuated in rats treated with ␣-FMH or mice with a genetic deletion of histamine H 1 receptors (Gotoh et al, 2009).…”
Section: Histamine-induced Loss Of Appetite Is An Adaptive Anorexiamentioning
confidence: 99%
“…Reduced estrogen production during menopause is believed to be a major cause for increased body fat and one factor contributing to increased risk for obesity in older females (1). Modification of GI microbiota may alleviate obesity by controlling energy expenditure and storage.…”
Section: Introductionmentioning
confidence: 99%